2010
DOI: 10.1371/journal.pone.0012011
|View full text |Cite
|
Sign up to set email alerts
|

PDE8 Regulates Rapid Teff Cell Adhesion and Proliferation Independent of ICER

Abstract: BackgroundAbolishing the inhibitory signal of intracellular cAMP by phosphodiesterases (PDEs) is a prerequisite for effector T (Teff) cell function. While PDE4 plays a prominent role, its control of cAMP levels in Teff cells is not exclusive. T cell activation has been shown to induce PDE8, a PDE isoform with 40- to 100-fold greater affinity for cAMP than PDE4. Thus, we postulated that PDE8 is an important regulator of Teff cell functions.Methodology/Principal FindingsWe found that Teff cells express PDE8 in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 72 publications
4
90
0
2
Order By: Relevance
“…This site has been previously reported to regulate ARHGEF2 activity (40). Moreover, ARHGEF2-dependent RhoA activity also has been shown to regulate the uropod of migrating T cells (71), in accordance with the report by Vang et al (88) that PDE8 inhibition caused a decrease in T-cell motility. In the current study, the combination of PDEs 1, 7, and 8 showed the largest increase in ARHGEF2 phosphorylation.…”
Section: Biological Processes Regulated By Different Pde-regulatedsupporting
confidence: 87%
“…This site has been previously reported to regulate ARHGEF2 activity (40). Moreover, ARHGEF2-dependent RhoA activity also has been shown to regulate the uropod of migrating T cells (71), in accordance with the report by Vang et al (88) that PDE8 inhibition caused a decrease in T-cell motility. In the current study, the combination of PDEs 1, 7, and 8 showed the largest increase in ARHGEF2 phosphorylation.…”
Section: Biological Processes Regulated By Different Pde-regulatedsupporting
confidence: 87%
“…Rolipram (Enzo Life Sciences, New York, NY) is a selective PDE4 inhibitor that does not distinguish between PDE4 isoforms. PF-04957325 (Pfizer, New York, NY) is a selective PDE8 inhibitor that will inhibit PDE8A and PDE8B with similar affinities and was a gift from the manufacturer (structure published in Vang et al, 2010). IBMX (Sigma-Aldrich) is a nonselective PDE inhibitor.…”
Section: Methodsmentioning
confidence: 99%
“…In this study the EBC proteomic composition of the 79 donors, including patients with different pathologies of the respiratory system has been investigated. Cytoskeletal keratins type II (1, 2, 3, 4, 5, 6) and cytoskeletal keratins the type I (9,10,14,15,16) were invariant for all samples. Analyzing the frequency of occurrence of proteins in different groups of examined patients, several categories of protein have been recognized: found in all pathologies (Dermcidin, Alpha-1-microglobulin, SHROOM3), found in several pathologies (CSTA, LCN1, JUP, PIP, TXN), and specific for a single pathology (PRDX1, Annexin A1/A2).…”
Section: Proteomic Analysis Of Exhaled Breath Condensate For Diagnosimentioning
confidence: 92%
“…Во всех группах с различной частотой встречаемости присутствовали цитоскелетные кератины II типа (1, 2, 3, 4, 5, 6) и цитоскелетные кератины I типа (9,10,14,15,16). Примерно с одинаковой частотой во всех рассматриваемых группах доноров были идентифицированы такие белки, как иммуноглобулин альфа, кинниноген, сывороточный альбумин, цинк-альфа2-гликопротеин, лизоцим.…”
Section: результаты и обсуждениеunclassified
See 1 more Smart Citation